Identification of discrete-time output error model for industrial processes with time delay subject to load disturbance. (February 2017) - Dong, Shijian; Liu, Tao; Wang, Wei; Bao, Jie; Cao, Yi
Highlights: Output error model identification for industrial processes with time delay. Load disturbance response is viewed as a dynamic parameter for estimation. Dual adaptive forgetting factors are introduced for recursive identification. A one-dimensional searching algorithm ensures the optimal time delay estimation. The convergence of model parameter estimation is analyzed with a proof. Abstract: In this paper, a bias-eliminated output error model identification method is proposed for industrial processes with time delay subject to unknown load disturbance with deterministic dynamics. By viewing the output response arising from such load disturbance as a dynamic parameter for estimation, a recursive least-squares identification algorithm is developed in the discrete-time domain to estimate the linear model parameters together with the load disturbance response, while the integer delay parameter is derived by using a one-dimensional searching approach to minimize the output fitting error. An auxiliary model is constructed to realize consistent estimation of the model parameters against stochastic noise. Moreover, dual adaptive forgetting factors are introduced with tuning guidelines to improve the convergence rates of estimating the model parameters and the load disturbance response, respectively. The convergence of model parameter estimation is analyzed with a rigorous proof. Illustrative examples for open- and closed-loop identification are shown to demonstrate the effectiveness and merit of the proposed identification method.